Perancangan Dashboard TX Compliance pada PT X sebagai Sarana Monitoring Persiapan Menuju Industri 4.0 - Alexander William Brillianata Setiadi; Siana Halim (Jurnal Titra, 2022)
This research aims to design a TX compliance dashboard in PT X. TX is an asset tracking application in PT X which is applied for monitoring filling station operational activities on gas cylinder products. However, there are several problems in information visualization, such as long and complicated data processing and visualization that do not give sufficient information for analysis and decision-making activities. These problems can be solved by designing a TX compliance dashboard that is integrated with data processing software. The purpose of dashboard design is to visualize all performance assessments regarding the implementation of TX. Data processing is done based on TX and ERP transaction data updated weekly, using software to increase data processing accuracy and speed. The processed data is integrated into the dashboard as a data visualization tool. Overall, the TX compliance dashboard can answer the needs of fill monitoring, delivery monitoring, transaction verification rate, cylinder scanning violation, and GPS-related violation.